Intensive care nurses’ experiences of teamwork during the covid-19 pandemic. a qualitative study. - Jeanette Eckerblad; Åsa Dorell; Helen Conte (BMC Nursing)
Abstract Background Teamwork is a core competence for all health care professionals and quality of care is a vital outcome. The pandemic backdrop of 2020–2022 led to initial chaos and adaptation of the nurses’ roles and responsibilities in the intensive care unit. Therefore, the purpose was to describe the intensive care nurses’ experiences of working in teams during the Covid-19 pandemic and discussing the results through the lens of transitiontheory. Methods Individual and semi-structured interviews were conducted with 16 intensive care nurses. The interview transcripts were analysed using Braun & Clarke’s six-step inductive thematic analysis. Results The intensive and critical care nurses’ experiences during the first 18 months of the Covid-19 pandemic captured chronological and conceptual commonalities, which were represented in three themes, “Losing the security of the ICU team”, “Having time to adapt and finding structure for collaborative work”, and “Gaining professional growth through adapting collaborative work to contextual challenges”. Conclusion Losing the security of the intensive care unit team, having to adapt to constant changes, and the need to provide care to an increased number of critically ill patients led to a sense of being left to manage on their own. The intensive care unit nurses missed the interprofessional collaboration that had previously been a core part of their professional role. The adaptability and willingness to find solutions helped nurses regain control, manage the challenges they faced and find new ways to collaborate. Clinical trial number Not applicable.